Effectiveness of Crude Extracts from Aromatic Plants against Crop’s Insect Infestation - Bin Steven @ Hanafiah, Arif Izwandy; Leng, Lee Yit; Hani, Nurul Wahida; Abdul Razak, Norawanis; Ismail, Ras Izzati; Makhtar, Nur Lailina (Advanced and Sustainable Technologies (ASET), 2026)
Agricultural productivity and food security are increasingly threatened by insect infestations, particularly in vegetable crops. The widespread use of synthetic insecticides raises concerns regarding human health, environmental pollution, and biodiversity loss, prompting the need for sustainable alternatives. This study evaluates the effectiveness of crude extracts from turmeric, pandan, lemongrass, and mint as biopesticides in Amaranthus viridis. The objectives were to assess their effects on plant weight, insect population, and leaf infestation. Crude extracts were prepared by water bath extraction and applied at a 1:4 ratio in a field experiment. Insect identification and observations were conducted over 17 days. Results indicated that all treatments showed varying levels of effectiveness. Lemongrass extract significantly enhanced plant growth and yield, while mint extract was the most effective in reducing insect infestations. Additionally, some treatments attracted beneficial insects, suggesting ecological benefits. These findings demonstrate the potential of aromatic plant extracts as eco-friendly alternatives to synthetic pesticides. This study contributes to the United Nations Sustainable Development Goals, particularly SDG 2 (Zero Hunger), SDG 3 (Good Health and Well-being), and SDG 12 (Responsible Consumption and Production), by promoting sustainable and safe agricultural practices.